Emotional Intelligence and Problems Faced By Prospective Physical Science Teachers During Internship - Priscilla; Mohaideen, Rasul (Journal of Neonatal Surgery, 2025)
The impact of emotional intelligence is studied in various fields but is less applied in the field of internship undergone by prospective teachers, with importance given to physical science students. The present study is aimed to find the impact of emotional intelligence on the problems faced by prospective physical science teachers during internship. The sample consisted of 300 prospective physical science teachers undergoing internship. Descriptive Survey method was used and Mangal Emotional Intelligence Inventory (2004) and Questionnaire for problems faced by prospective physical science teachers were used as tools to collect data from the prospective teachers. Percentage Analysis and Correlation were used to analyse and interpret the data. The findings of the study indicate that the emotional intelligence and problems faced during internship were moderate and there was negative correlation between emotional intelligence and problems faced during internship.